Age, Growth, and Sexual Maturity of the Crocodile Shark, Pseudocarcharias kamoharai, From the Eastern Atlantic Ocean - Kindong, Richard; Wang, Haozhan; Wu, Feng; Dai, Xiaojie; Tian, Siquan (Frontiers in Marine Science, 2020)
To better manage fish populations, scientists and fisheries managers use age and growth studies to conduct stock assessments or provide management advice. However, many non-targeted species, important to the marine ecosystem, such as Pseudocarcharias kamoharai still lack such studies which impede comprehensive management of the fisheries. This study presents the age, growth, and sexual maturity of this species from the Tropical Eastern Atlantic Ocean (TEA) by examining vertebral samples. All samples were collected by Chinese Tuna Fishery Scientific Observers between November 2012 and May 2020, with sizes ranging from 46 to 101 cm fork length (FL). Four age determination approaches applied on whole and sectioned vertebral centra were compared. Four growth models fitted to the age data were also compared and the AIC was used to select the most plausible model. Whole vertebral centra stained with alizarin red S solution showed clearer growth band-pairs, and age ranged from 2 to 10 years (females) and from 2 to 11 years (males). The three-parameter von Bertalanffy growth function presented the best fit to describe the growth of this species. The obtained parameters for males were L∞ = 110.4 cm FL, K = 0.26 year-1 and L∞ = 108.3 cm FL, K = 0.29 year-1 for females. Females reached their size at 50% maturity (FL50%) larger than males (80.5 and 74.5 cm FL, respectively). The estimated longevities were 11.95 and 13.33 years for females and males, respectively. More work is needed regarding P. kamoharai in different Oceans, though, this study adds significant life-history information that can contribute to the management and conservation of the species.